The progress and prospect of environmental impact assessment system in India: from 1994 to 2020 notification - Ziaul Islam; Shuwei Wang (EQA, 2022)
In this short communication, we review the Environmental Impact Assessment (EIA) law of India from the 1994 to 2020 amendments. Our study shows that the EIA system of India is undergoing a transitional period. In the 1994 EIA Notification, public hearings are included that ensure the voice of the general people in decision-making for sustainable development. A reverse scenario has been seen in the EIA Notification of 2006 and 2020, respectively, where public participation is almost overlooked, and the high interests of the proponents are taken into consideration. Issues like post-facto clearance and limiting public consultations regarding the proposed projects are the biggest obstacles in EIA Notification 2020. Our study also reveals that although the recent amendment quickens obtaining the Environmental Clearance (EC), it brings forth other problems like corruption, lack of transparency, false and fabricated data, poor monitoring etc that hinder the way of effective EIA system in India.